The Ancient mind elements of cognitive archaeology - Renfrew, Colin 1937-.; Zubrow, Ezra B. W. (Cambridge [England] Cambridge University Press, 1994)
"Collection of articles seeks to define a scientific approach to prehistoric cognition. In an important paper, Marcus and Flannery look at the evolution of Zapotec religion and ritual and the transformation of Monte Albán and the Zapotec state"--Handbook of Latin American Studies, v. 57. |u http://www.loc.gov/hlas
Keywords: Archaeology; Cognition and culture